40.0k views
5 votes
A(c-b)=d solve for varible c

2 Answers

0 votes


a(c-b)=d\qquad\text{divide both sides by }\ a\\eq0\\\\c-b=(d)/(a)\qquad\text{add}\ b\ \text{to both sides}\\\\\boxed{c=(d)/(a)+b}

User Andrew Nesbitt
by
4.6k points
2 votes

Answer:


\text{c}=(d + ab)/(a)

Explanation:

Remove the brackets.

ac - bc = d

Add bc to both sides

ac = d + bc

Divide by a


(ac)/(a)=(d + ab)/(a)

The "a"s cancel and you are left with the answer.


\text{c}=(d + ab)/(a) Answer


User Arturgrigor
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.